International pediatric surgery partnerships in sub-Saharan Africa: a scoping literature review - Alison Woods; Charles Shofner; Bethany Hodge (Taylor & Francis Group, 2022)
Background Sub-Saharan Africa (SSA) faces a critical shortage of pediatric surgical providers. International partnerships can play an important role in pediatric surgical capacity building but must be ethical and sustainable. Objective The purpose of this study is to perform a scoping literature review of international pediatric surgery partnerships in SSA from 2009 to 2019. We aim to categorize and critically assess past partnerships to aid in future capacity-building efforts. Methods We performed a scoping literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines. We searched the PubMed and Embase databases for articles published from 2009 to 2019 using 24 keywords. Articles were selected according to inclusion criteria and assessed by two readers. Descriptive analyses of the data collected were conducted in Excel. Results A total of 2376 articles were identified. After duplicates were removed, 405 articles were screened. In total, 83 articles were assessed for eligibility, and 62 were included in the review. The most common partnership category was short-term surgical trip (28 articles, 45%). A total of 35 articles (56%) included education of host country providers as part of the partnership. Only 45% of partnerships included follow-up care, and 50% included postoperative outcomes when applicable. Conclusions To increase sustainability, more partnerships must include education of local health-care providers, and short-term surgical trips must be integrated into long-term partnerships. More partnerships need to report postoperative outcomes and ensure follow-up care. Educating peri-operative providers, training general surgeons in common pediatric procedures, and increasing telehealth use are other goals for future partnerships.